2022
DOI: 10.1038/s41746-022-00718-2
|View full text |Cite
|
Sign up to set email alerts
|

Emerging approaches to redressing multi-level racism and reproductive health disparities

Abstract: This commentary examines the impact of multi-level racism on reproductive health disparities in the United States. Multi-level racism and its impact on reproductive health over the lifespan are described on a societal, community, and individual level. To advance, we recommend using the Remove, Repair, Restructure, Remediate (R4P) approach combined with the Retrofit, Reform, and Reimagine (3R) model to address multiple forms of racism. Emergent policies and actions are identified to proceed towards health equit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
(32 reference statements)
0
7
0
Order By: Relevance
“…This study adds to an ongoing discussion of how digital health transformation might contribute to existing health disparities . Disparities in technology use may emerge through differential access for patients with limited health literacy and members of racial and ethnic minority groups, as documented during the diffusion of patient portal use and telehealth .…”
Section: Discussionmentioning
confidence: 99%
“…This study adds to an ongoing discussion of how digital health transformation might contribute to existing health disparities . Disparities in technology use may emerge through differential access for patients with limited health literacy and members of racial and ethnic minority groups, as documented during the diffusion of patient portal use and telehealth .…”
Section: Discussionmentioning
confidence: 99%
“… 41 Comprehensive approaches inclusive of patient stakeholders are key to avoid proposing solutions that could inadvertently cause harm. 51 , 52 We can glean valuable information from these data, informing future obstetric quality measures and interventions. Antepartum anemia is modifiable, and addressing anemia through an equity lens has potential for closing disparity gaps in SMM.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple models have been proposed to address inequities at multiple levels of care, including factors at the level of healthcare delivery systems, research, individual providers, policymakers, and payers. 32 , 33 , 34 An example of one of these considerations is that many digital programs are exclusively in English, which may alienate patients who are non-English speakers from engaging fully with these programs. 32 , 34 One study from California of >84,000 patients found that patients with limited English proficiency had half the odds of telehealth use compared with proficient English speakers (4.8% vs 12.3%).…”
Section: Opportunities To Reduce Racial Inequities In Carementioning
confidence: 99%